STRATEGI RUMAH TANGGA TRANSMIGRAN DALAM MEMENUHI KEBUTUHAN DASAR DI PROVINSI SUMATERA SELATAN (TRANSMIGRANT HOUSEHOLD STRATEGY IN ORDER TO FULFIL THE BASIC NEED IN SOUTH SUMATERA PROVINCE) - M Yamin; Ida Bagoes Mantra; M Maksum; Slamet Hartono (Agro Ekonomi, 2002)
The objective of this research is to know the household strategy in order to fulfill the household the basic need. The research is done in South Sumatra Province with on settlement unit sample there are taken purposively based on the up land and low land, the new (maximum for seven years) and old settlement (more then seven years). The samples of households are taken randomly from each unit at about 15% from the population.The method of analysis are using regression OLS, and using coefficient variation.Permanent consumption is on the primary food level while temporary consumption consist of clothes, education, furniture, er cetera. In old settlement, permanent income in up land comes from the farm and off farm, while in low land comes only from the farm. The short-term strategy is that because of the limitation (Oransmigran's income, they postpone or sacrifice the other necessities. The longterm strategy will change due to the growing age of the settlement from only specializing on food crop to cash crop. However, the age of settlement studied is not enough to grow perennial cash crop.